2019
DOI: 10.1177/1352458519881760
|View full text |Cite
|
Sign up to set email alerts
|

Word-finding difficulty is a prevalent disease-related deficit in early multiple sclerosis

Abstract: Background: Persons with multiple sclerosis (MS) commonly report word-finding difficulty clinically, yet this language deficit remains underexplored. Objective: To investigate the prevalence and nature of word-finding difficulty in persons with early MS on three levels: patient report, cognitive substrates, and neuroimaging. Methods: Two samples of early MS patients ( n = 185 and n = 55; ⩽5 years diagnosed) and healthy controls ( n = 50) reported frequency/severity of cognitive deficits and underwent objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 35 publications
(44 reference statements)
1
42
1
Order By: Relevance
“…This test shares some cognitive processes with fluency tasks, such as search, selection, and word retrieval, but with a lower degree of time restriction. Although language was usually considered to be largely preserved in MS, recent studies using novel tests evaluating the speed to lexical access have shown frequent impairment even in early stages ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…This test shares some cognitive processes with fluency tasks, such as search, selection, and word retrieval, but with a lower degree of time restriction. Although language was usually considered to be largely preserved in MS, recent studies using novel tests evaluating the speed to lexical access have shown frequent impairment even in early stages ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 185 MS patients were included in this study (The Reserve against Disability in Early MS (RADIEMS) Cohort). 22 Patients were aged 20–50 years and diagnosed with relapsing-remitting MS (RRMS) ( N = 163) or clinically isolated syndrome (CIS with ⩾1 brain lesion, N = 20) 23 for ⩽5.0 years were enrolled from Corinne Goldsmith Dickinson Center for MS at Mount Sinai Hospital and Columbia University Irving Medical Center. Exclusion criteria included pregnancy, clinical relapse within 6 weeks, non-proficient in English, history of other neurologic condition, neurodevelopmental disorder, diagnosed learning disability, schizophrenia, bipolar disorder, substance abuse disorder, or current major depressive disorder (please see Table 1 for detailed sample demographics).…”
Section: Methodsmentioning
confidence: 99%
“…A comprehensive battery of cognitive tests across multiple domains and comprising the minimal neuropsychological assessment of MS (MACFIMS) was administered. 22 Raw SDMT (oral version) scores from this battery were regression corrected to control for age, sex, education, and intelligence quotient (IQ). Z -scores were calculated using 50 age, sex, and education-matched healthy controls.…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, these persons experienced a reduced quality of life than did those without language impairment ( El-Wahsh et al, 2020 ). Several studies reported evidence that word (verb and noun) finding problems are common in MS (e.g., Sepulcre et al, 2011 ; Kambanaros et al, 2017 ; Brandstadter et al, 2019 ). Brandstadter et al (2019) found that word-finding difficulties attested in MS are linked to left parietal cortical thinning.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported evidence that word (verb and noun) finding problems are common in MS (e.g., Sepulcre et al, 2011 ; Kambanaros et al, 2017 ; Brandstadter et al, 2019 ). Brandstadter et al (2019) found that word-finding difficulties attested in MS are linked to left parietal cortical thinning. It should be noted, however, that there are still gaps in our knowledge regarding both the neural substrate of language impairment in MS and the aspects of language affected by MS. Morphosyntactic production, for example, has not been explored adequately thus far.…”
Section: Introductionmentioning
confidence: 99%